Basic procedural justice: tool of transition toward mini-mally decent societies (2010)
From the reconstruction of the approaches of Rodrigo Uprimny, Rajeev Bhargava and Stuart Hampshire on transitional justice models, it will be posed that the minimally decent society concept, coined by the second author, sheds new lights on the discussions